Impact of Objective Structured Clinical Examination on Knowledge and Perception among Nursing Students from Selected Colleges in Metropolitan City - Saisagar Kshirsagar, Shweta (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of this study was to assess impact of objective structured clinical examination (OSCE) on knowledge and perception among nursing students from selected. Materials and Methods: The research design adopted for this study was experimental one group pre-test and post-test research design with qualitative and quantitative research approach. The source of data collection process was done using primary and secondary data from nursing students in selected colleges of Mumbai and New Mumbai region. Three hundred nursing students from 3rd to 4th year basic BSC nursing, 3rd year general nursing and midwifery, and 1st year post basic BSC nursing were recruited in the study using non-probability convenient sampling technique. Tool used consisted of demographic data, opinionative to assess the perception of nursing students about OSCE, suggestions by the respondents, and rating of OSCE. ANOVA is included in the analysis of quantitative research and interest for the discrepancy in performance. Data were analyzed using descriptive and inferential statistics. Fishers exact test used for association between post insight score with selected demographic variables Results: The results of this study showed that mean difference between pre-insight and post-insight scores is statistically significant as the calculated T value is 84.85 (P = 0.0026) which is greater than the T table value of 1.06 at a significance level of 0.05 with a degree of freedom being 281. The knowledge among the students has been increased after providing the knowledge. Conclusion: The findings of the study concluded that OSCE is has a positive impact on nursing students’ knowledge and perception.